"Don't give up on me": critical mentoring pedagogy for the classroom building students' community cultural wealth. Issue 1 (2nd January 2016) - Liou, Daniel D.; Martinez, Antonio Nieves; Rotheram-Fuller, Erin
Abstract : This one-year ethnographic case study focused on students of color from a West Coast High School who faced a variety of academic challenges. Collectively, they shared perspectives on school improvement, and among the recommendations was the importance of mentorship in the classroom to develop students' aspirational, navigational, and informational capital for academic resiliency, high expectations, and success. This article highlights the perspectives of multiple stakeholders, such as students and teachers, on the qualities of mentorship practices. Using these data, a framework was developed to promote mentoring as an interrelated process in classroom instruction to ignite a new perspective on school reform. In this particular context, this study concludes that these students of color viewed mentorship as a critical component that was often missing in their high school careers. In an effort to improve students' experiences in the classroom, this article argues that teachers must develop critical mentoring skills, beyond what is traditionally considered as mentoring services, as a pedagogical tool to assist students to overcome their academic challenges and achieve school success.